Academy of Management Perspectives (JSTOR)
The journal provide accessible articles about important issues concerning management and business. AMP articles are aimed at the non-specialist academic reader, not practicing managers, and rely on evidence as opposed to theory or opinion for their arguments.
Keywords: Business, Business & Economics, Management & Organizational Behavior